2022
DOI: 10.1051/bioconf/20224903004
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Ameliorates Liver Function in Association with Bax Downregulation, P53 Downregulation and Bcl-2 Upregulation in Diabetic Wistar Rat

Abstract: Hyperglycemia in Diabetes mellitus (DM) induces oxidative stress and mitochondrial disruptions in the liver, thereby triggering apoptosis through Bcl-2 family signaling. Excessive apoptosis leads to liver dysfunction. Chlorogenic acid (CGA) was elucidated in this study in preventing liver dysfunction as a progression of DM. The diabetic model was conducted in Wistar rats, divided into six groups. Blood examinations were done to measure the levels of blood glucose, SGOT, and SGPT. The liver was harvested for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As a result, AEEL showed an improvement effect on apoptosis by downregulating the expression levels of apoptosisrelated factors and upregulating the expression levels of anti-apoptosis-related factors in DSS-induced mice (Figure 9). According to Setyaningsih et al (2022), chlorogenic acid inhibits apoptosis by decreasing the expression level of BAX and increasing the expression level of BCl-2 in streptozotocin (STZ)-induced rats [60]. Cheng et al (2022) reported that E. ulmoides extract inhibits apoptosis by downregulating the expression level of BAX and cleaved caspase 3 and upregulating the expression level of BCl-2 in spinal cord-injury rats [61].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, AEEL showed an improvement effect on apoptosis by downregulating the expression levels of apoptosisrelated factors and upregulating the expression levels of anti-apoptosis-related factors in DSS-induced mice (Figure 9). According to Setyaningsih et al (2022), chlorogenic acid inhibits apoptosis by decreasing the expression level of BAX and increasing the expression level of BCl-2 in streptozotocin (STZ)-induced rats [60]. Cheng et al (2022) reported that E. ulmoides extract inhibits apoptosis by downregulating the expression level of BAX and cleaved caspase 3 and upregulating the expression level of BCl-2 in spinal cord-injury rats [61].…”
Section: Discussionmentioning
confidence: 99%